2005
DOI: 10.1080/10409230590935479
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Control the Tissue-Specific Transcription of the Gene for Phosphoenolpyruvate Carboxykinase-C

Abstract: Transcription of the gene for PEPCK-C occurs in a number of mammalian tissues, with highest expression occurring in the liver, kidney cortex, and white and brown adipose tissue. Several hormones and other factors, including glucagon, epinephrine, insulin, glucocorticoids and metabolic acidosis, control this process in three responsive tissues, liver, adipose tissue, and kidney cortex. Expression of the gene in these three tissues in regulated in a different manner, responding to the specific physiological role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
135
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(145 citation statements)
references
References 138 publications
7
135
2
1
Order By: Relevance
“…Induction of AMPK in hepatoma cells also decreases PEPCK and G-6-Pase transcription, likely in an insulin-independent manner [104]. AMPK is not known to be activated by insulin, raising the possibility that insulin and AMPK regulate PEPCK by different and, perhaps, converging pathways [70]. AMPK may prevent insulin resistance in part by inhibiting factors that antagonise insulin signalling [100].…”
Section: Carbohydrate-response Element-binding Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Induction of AMPK in hepatoma cells also decreases PEPCK and G-6-Pase transcription, likely in an insulin-independent manner [104]. AMPK is not known to be activated by insulin, raising the possibility that insulin and AMPK regulate PEPCK by different and, perhaps, converging pathways [70]. AMPK may prevent insulin resistance in part by inhibiting factors that antagonise insulin signalling [100].…”
Section: Carbohydrate-response Element-binding Proteinmentioning
confidence: 99%
“…SREBP-1c and SREBP-2 are the predominant subtypes in the rodent and human liver [67]. The main role of SREBP-2 is cholesterol synthesis, whereas SREBP-1c activates a complete programme of hepatic fatty acid synthesis [68] and reciprocally inhibits the expression of the gene for PEPCK when carbohydrates are abundant [69,70]. Overexpression of the gene for SREBP-1c leads to fatty liver in mice [71].…”
Section: Sterol Regulatory Element-binding Protein 1cmentioning
confidence: 99%
See 1 more Smart Citation
“…The compensatory upregulation of G6pc on PP1was ineffectual because there were little glycogen reserves upon which the enzyme could act. The up-regulation of liver Pck1, whose product is the rate limiting step of gluconeogenesis from non-carbohydrate sources (Chakravarty et al 2005), on E19 and PP1 was also insufficient to alleviate the hypoglycemia. We also observed a dramatic depletion of lipid stores in BAT and the reduced expression of two BAT-specific thermogenic genes, Pgc1a and Ucp1.…”
Section: Loss Of Energy Homeostasis In Cbx3 Hypo/hypo Neonatesmentioning
confidence: 99%
“…For example, the gene encoding phosphoenolpyruvate carboxykinase (PEPCK), expressed in liver and other tissues, has upstream cis-elements for several transcription factors and is under complex, tissue-specific and hormone-dependent control in keeping with its critical role in gluconeogenesis. 16 While little information exists on the mechanism of regulation of Glu1, earlier studies using in vitro transcription 17 and analysis of HNF1␣-null mice 18 revealed that the Cyp2e1 gene is controlled by the liver-enriched transcription factor HNF1␣. Expression of the gene encoding CYP1A2 is also controlled by HNF1␣ as well as other transcription factors.…”
mentioning
confidence: 99%